The para judo competitions: reflections and possible strategies to improve accessibility in official tournaments - Lima Kons, R.; Haegele, J. (Managing Sport and Leisure, 2024)
This study provides a comprehensive analysis focusing on three critical facets: (1) evidence-based classification in Paralympic sports, with particular attention to recent changes in Para judo; (2) the rules and structure governing judo competitions; and (3) proposals aimed at enhancing the competitive environment, specifically emphasizing accessibility for judo athletes with visual impairments. We meticulously examine the current competition framework's effectiveness in promoting inclusive participation and equitable opportunities for athletes with visual impairment. Furthermore, innovative recommendations are proposed to address accessibility challenges within the competitive landscape, drawing insights from accessibility perspectives. Our study contributes significantly to the discourse surrounding judo competition dynamics by addressing these focal points. It advocates for meaningful enhancements prioritizing inclusivity and equal access for all athletes, irrespective of visual impairment. These proposals aim to foster a competitive environment that accommodates diverse needs and ensures that judo remains accessible and welcoming to athletes with visual impairment. Ultimately, our study seeks to advance the broader goal of creating a more inclusive and equitable sports environment for all participants.